1960
DOI: 10.2172/4186720
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evaluation of the Radiation Protection Afforded by Typical Oak Ridge Homes Against Distributed Sources

Abstract: This report is published in the interest of providing information which may prove of value to the reader in his study of effects data derived principally from nuclear weapons tests. This document is based on information available at the time of preparation which may have subsequently been expanded and re-evaluated. Also, in preparing this report for publication, some classified material may have been removed. Users are cautioned to avoid interpretations and conclusions based on unknown or incomplete data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1

Year Published

1963
1963
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 0 publications
1
10
1
Order By: Relevance
“…All of the measurements were collected before decontamination began. It is noted that the difference in methods of selecting the locations for the indoor measurements and of obtaining the outdoor dose between in this study and in the experimental study utilizing 60 Co reported in the CEX-59.13 16 . For the latter, the readings of dosimeters placed along the axis which ran through the center of the house were used as the indoor dose and the infinite-plane dose rate at a height of 1 m was used as the outdoor dose.…”
Section: Methodsmentioning
confidence: 75%
See 2 more Smart Citations
“…All of the measurements were collected before decontamination began. It is noted that the difference in methods of selecting the locations for the indoor measurements and of obtaining the outdoor dose between in this study and in the experimental study utilizing 60 Co reported in the CEX-59.13 16 . For the latter, the readings of dosimeters placed along the axis which ran through the center of the house were used as the indoor dose and the infinite-plane dose rate at a height of 1 m was used as the outdoor dose.…”
Section: Methodsmentioning
confidence: 75%
“…The IAEA-TECDOC-1162 document gives the representative reduction (shielding) factor range of 0.2 to 0.5 for one- and two-story wooden frame homes. This range was determined by experimental results of full scale structures using a radioactive source 15 16 . The frequency reduction factor distribution measured experimentally for wooden frame houses, which is referred to as the CEX-59.13 16 , is also plotted in Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A collection of lightweight, in-use, single family residences (80 to 250 m 2 footprint) were studied using Co-60 roof and ground sources [46], [47]. The exterior wall material ranged from wood siding, Cemesto panels (Figure B10), stucco, and concrete block.…”
Section: Single Family Residencesmentioning
confidence: 99%
“…Even minimal shielding can afford a high level of protection in most areas contaminated by local fallout (12,26,36,20). Further, fallout accumulates in a visible layer of dust, ashes, and mud, and can be removed by sweeping and washing.…”
mentioning
confidence: 99%